Ferulic acid ameliorated placental inflammation and apoptosis in rat with preeclampsia - Yuanyuan Chen; Fengxia Xue; Cha Han; Huiyun Yang; Lulu Han; Ke Li; Jie Li; Qian Xu; Zengyan Li; Bibo Yuan; Limin Yu; Xiaoli Gao; et al. (Clinical and Experimental Hypertension, 2019)
Preeclampsia (PE) occurs specifically during pregnancy characterized by new-onset hypertension. The pathogenesis of PE was complicated, and inflammation may be central to the pathogenesis of PE. Ferulic acid (FA) is recognized to prevent cell damage and apoptosis induced by oxidative stress and inflammation. In our study, we used NG-nitro-l-arginine methyl ester (L-NAME)-induced rat model of PE to investigate whether FA improved PE and its possible mechanism. We found that FA significantly reduced blood pressure, urine volume, and urinary protein level in rats with PE. Meanwhile, FA decreased L-NAME induced higher expression of circulating TNF-α、IL-6、IL-1β and PlGF, it reduced placental TNF-α and NF-κB p65. Furthermore, FA rescued L-NAME induced decreasing expression of IL-4 and IL-10 expression in the circulation and placenta of rats. FA also ameliorated placental apoptosis in L-NAME induced rats by increasing Bcl-2 whereas decreasing Bax expression in placenta. It suggested FA as a potential candidate for the treatment of various disorders including L-NAME induced preeclampsia in rats through decreasing placental inflammation and apoptosis.